The Impact of Social Change on the Practice of Polygamy in Modern Society: A Review of Islamic Family Law - Darwin Wibowo Sihombing; Muhammad Firza (AT-TAFAHUM: Journal of Law, 2021)
This study aims to analyze the impact of social change on the practice of polygamy in the context of modern society and to examine the relevance of Islamic family law in implementing these regulations. Using qualitative descriptive methods, this study involved in-depth interviews with religious leaders, legal practitioners, and individuals involved in the practice. Furthermore, this study considered the social, cultural, and economic dynamics that influence individual decisions in pursuing the practice. The results indicate that public awareness of women's rights and the importance of social justice is increasing, significantly changing their perspectives on polygamy. Although Islamic law permits polygamy under conditions of fairness, practice often falls short of these criteria. Many families experience dissatisfaction, internal conflict, and psychological impacts due to unfair treatment between wives. This study concludes that achieving justice in the practice of polygamy requires more comprehensive legal education, strong advocacy for individual rights, and strengthened oversight and enforcement mechanisms. Therefore, this research is expected to provide broader insights for policymakers and the public in creating more just, humane, and relevant solutions to the practice of polygamy in the modern era.